Theoretical investigation of GaAsBi/GaAsN tunneling field-effect transistors with type-II staggered tunneling junction. (June 2017) - Wang, Yibo; Liu, Yan; Han, Genquan; Wang, Hongjuan; Zhang, Chunfu; Zhang, Jincheng; Hao, Yue
Abstract: We investigate GaAsBi/GaAsN system for the design of type-II staggered hetero tunneling field-effect transistor (hetero-TFET). Strain-symmetrized GaAsBi/GaAsN with effective lattice match to GaAs exhibits a type-II band lineup, and the effective bandgap E G, eff at interface is significantly reduced with the incorporation of Bi and N elements. The band-to-band tunneling (BTBT) rate and drive current of GaAsBi/GaAsN hetero-TFETs are boosted due to the utilizing of the type-II staggered tunneling junction with the reduced E G, eff . Numerical simulation shows that the drive current and subthreshold swing (SS) characteristics of GaAsBi/GaAsN hetero-TFETs are remarkably improved by increasing Bi and N compositions. The dilute content GaAs0.85 Bi0.15 /GaAs0.92 N0.08 staggered hetero-nTFET achieves 7.8 and 550 times higher I ON compared to InAs and In0.53 Ga0.47 As homo-TFETs, respectively, at the supply voltage of 0.3 V. GaAsBi/GaAsN heterostructure is a potential candidate for high performance TFET. Highlights: Strain-symmetrized GaAsBi/GaAsN nTFETs with effective lattice match to GaAs and type-II tunnel junction are designed. Performance of GaAsBi/GaAsN hetero-TFET is boosted with the increasing of Bi and N compositions. GaAs0.85 Bi0.15 /GaAs0.92 N0.08 hetero-TFET demonstrates an improved I ON and SS compared to the InAs homo-TFET.